Phytochemistry, antioxidant, anticancer, and acute toxicity of traditional medicinal food Biarum bovei (Kardeh) - Bassam Ali Abed Wahab; Zaenah Zuhair Alamri; Ahmed A.j. Jabbar; Ibrahim Abdel Aziz Ibrahim; Riyad A. Almaimani; Hussain A. Almasmoum; Mazen M. Ghaith; Wesam F. Farrash; Yahya A. Almutawif; Khalid Aidarous Ageeli; Soliman Mohammed Alfaifi; Rahaf Frehan Alharthi (BMC, 2023)
Abstract Background The Biarum species (Kardeh) has been consumed as a traditional functional food and medicine for decades. The current study investigates the phytochemistry, in-vitro and in-vivo bioactivities of methanol extracts of B. bovei. Methods The Gas-chromatography mass spectrophotometer (GS/GS-MS) was used to analyze the phytochemical profile of the methanol extracts of B. bovei leaves and corms. The B. bovei extracts (BBE) were also investigated for in-vitro antioxidant, anticancer, and in-vivo acute toxicity (2000 mg/kg) activities. Results The chemical profiling of BBE revealed mainly fatty acids, phytosterol, alcohols, and hydrocarbon compounds. Namely, Linoleic acid, eliadic acid, palmitic acid, 22,23-dihydro-stigmasterol, and campesterol. The antioxidant activity of BBE ranged between 0.24-3.85 μg TE/mL based on different assays. The extracts also exhibited significant anticancer activity against DU-145 (prostate cancer cells), MCF-7 (human breast adenocarcinoma), and HeLa (human cervical cancer) cell lines with IC50 values ranging between 22.73-44.24 μg/mL. Rats fed on 2000 mg/kg dosage of BBE showed absence of any toxicological sign or serum biochemical changes. Conclusion The detected phytochemicals and bioactivities of BBE scientifically backup the folkloric usage as an important source of nutraceuticals and alternative medicine for oxidative stress-related diseases and carcinogenesis inhibition.